2015
DOI: 10.1098/rspb.2014.2781
|View full text |Cite
|
Sign up to set email alerts
|

Subtropical mouse-tailed bats use geothermally heated caves for winter hibernation

Abstract: We report that two species of mouse-tailed bats (Rhinopoma microphyllum and R. cystops) hibernate for five months during winter in geothermally heated caves with stable high temperature (208C). While hibernating, these bats do not feed or drink, even on warm nights when other bat species are active. We used thermo-sensitive transmitters to measure the bats' skin temperature in the natural hibernacula and open flow respirometry to measure torpid metabolic rate at different ambient temperatures (T a , 16-358C) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 46 publications
1
22
0
Order By: Relevance
“…Interestingly, mouse-tailed bats (Rhinopoma) are even considered incapable of entering torpor during cold periods (Kulzer, 1965). Levin et al (2015) found that two species of mouse-tailed bats (Rhinopoma cystops, Rhinopoma microphyllum) hibernated in a geothermally heated cave in winter with a stable ambient temperature of 19-23.8 • C although colder caves were available. Both species showed the lowest torpor metabolic rate at ∼20 • C and aroused at ambient temperature below 16 • C (Levin et al, 2015).…”
Section: Different Triggers Of Torpor Usementioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, mouse-tailed bats (Rhinopoma) are even considered incapable of entering torpor during cold periods (Kulzer, 1965). Levin et al (2015) found that two species of mouse-tailed bats (Rhinopoma cystops, Rhinopoma microphyllum) hibernated in a geothermally heated cave in winter with a stable ambient temperature of 19-23.8 • C although colder caves were available. Both species showed the lowest torpor metabolic rate at ∼20 • C and aroused at ambient temperature below 16 • C (Levin et al, 2015).…”
Section: Different Triggers Of Torpor Usementioning
confidence: 99%
“…Levin et al (2015) found that two species of mouse-tailed bats (Rhinopoma cystops, Rhinopoma microphyllum) hibernated in a geothermally heated cave in winter with a stable ambient temperature of 19-23.8 • C although colder caves were available. Both species showed the lowest torpor metabolic rate at ∼20 • C and aroused at ambient temperature below 16 • C (Levin et al, 2015). Thus, the availability of warm caves has allowed them to expand their subtropical distribution range from semi-arid and warm regions in Asia and Africa into southern Israel, the northern edge of their distribution (Levin et al, 2008(Levin et al, , 2015.…”
Section: Different Triggers Of Torpor Usementioning
confidence: 99%
“…Intriguingly, during hibernation, organs resist injury from the above cycles of I-R [4,5]. The discovery that in certain species, hibernation takes place with the preservation of high body temperature is significant, since, in human I-R injury, body temperature remains stable [6]. Finally, the identification of certain primate hibernators makes the study of this phenomenon extremely interesting, as these species are evolutionarily close to humans [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…However, studies have demonstrated that these mammals resist warm I-R injury more than other phylogenetically related species that are unable to hibernate (8,9). Evidence has revealed hibernation in high ambient and body temperatures, a phenomenon observed even in primates (10,11). Therefore, besides resistance to cold I-R injury, resistance to warm I-R injury also occurs in certain hibernators, some of which are phylogenetically close to humans.…”
Section: Introductionmentioning
confidence: 99%